Frailty and health risks in an agricultural population, Chile 2014–2017. (May 2019) - Bustamante-Ara, Natalia; Villarroel, Luis; Paredes, Fabio; Huidobro, Andrea; Ferreccio, Catterina
Highlights: This study shows the potential severity of frailty in an agricultural population. Diabetes was strongly associated with frailty. Frail older adults, especially men, had higher risk of health event in a short-term. Objective measurements of frailty, the first step to design preventive strategies. Abstract: Background: Aging presents an emerging health and social challenge. We report the prevalence of frailty, its association with chronic diseases and the risk of hospitalization or death within 29 months. Methods: Cross-sectional and prospective study. From 2014 to 2017, we examined frailty in an agricultural population in Chile. We enrolled 619 individuals aged 60–74 years from the Maule Cohort. Measured frailty prevalence, based the presence of ≥3 of the five factors (unintentional weight loss, weakness, slowness, self-reported exhaustion, low physical activity). We explored chronic diseases as predictors of frailty with multinomial regression models (sex, age, and schooling adjusted), and the risk of hospitalization and mortality by frailty status, with Cox regression models and Kaplan-Meier survival curves. Results: 6% of participants were frail; women had higher prevalence of frailty (8.2%) than men (2.3%, <0.001). Diabetes was a risk factor of frailty (Relative Risk Ratio: 3.91; 95% CI: 1.84–8.32). The incidence of hospitalization was 32% in frail (Hazard Ratio, HR: 3.68; 95% CI: 1.77–7.63), 16% in pre-frail (HR: 1.91; 95% CI: 1.19–3.08) and 9% in robust participants. Among the participants, men had higher risk of hospitalization than women (7.1 and 4.1 per 1000 person-month, p = .014). In all mortality was higher among men than women (1.0 and 0.2 per 1000 person-month, p = .031). Conclusions: In this agricultural population, diabetes was main chronic disease as risk factor of frailty. Frail older adults had higher risk of hospitalization than robust people, and especially men, had higher risk of adverse health event in a short-term.